Beclin 1-Mediated Autophagy Is Potentiated by an Interaction with the Neuronal Adaptor FE65 - Wai Wa Ray Chan; Jessica Chow; Dennis Dik-Long Chau; Yuqi Zhai; Kwok-Fai Lau (Biology)
Autophagy is a vital cellular pathway in eukaryotic cells, including neurons, where it plays significant roles in neurodevelopment and maintenance. A crucial step in autophagy is the formation of the class III phosphatidylinositol 3-kinase complex 1 (PI3KC3-C1), which is essential for initiating autophagosome biogenesis. Beclin 1 is the key component of PI3KC3-C1, and its interactors have been reported to affect autophagy. The brain-enriched adaptor protein FE65 has been shown to interact with Alzheimer’s disease amyloid precursor protein (APP) to alter the processing of APP. Additionally, FE65 has been implicated in various cellular pathways, including autophagy. We demonstrate here that FE65 positively regulates autophagy. FE65, through its C-terminus, has been shown to interact with Beclin 1. Notably, the overexpression of FE65 enhances Beclin 1-mediated autophagy, whereas this process is attenuated in FE65 knockout cells. Moreover, the stimulatory effect of FE65 on Beclin 1-mediated autophagy is diminished by an FE65 C-terminus deletion mutant that disrupts the FE65–Beclin 1 interaction. Lastly, we have found that the FE65-Beclin 1 interaction modulates the kinase activity of the PI3KC3-C1 complex. Together, we have identified FE65 as a novel Beclin 1 interactor, and this interaction potentiates autophagy.